Pengaruh Pengalaman Merek Terhadap Loyalitas Merek Pada Lipstik Merek Maybelline (Studi Pada Mahasiswi Universitas Negeri Padang) - Rahmadhani, Tia; Rahmidani, Rose (Jurnal Salingka Nagari, 2023)
The purpose of this study is to determine the effect of brand experience on brand loyalty on Maybelline brand lipstick among Universitas Negeri Padang students, This is known as causative research. The population in this study was Universitas Negeri Padang students, and the number of samples determined using the Cochran formula was 97. Purposive sampling is used in this study. The data used is the type of primary data obtained by distributing questionnaires to Universitas Negeri Padang students who met certain criteria, namely having purchased a minimum amount of Maybelline lipsticks. The study found that brand experience had a significant and positive effect on brand loyalty.